Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1177/03635465990270011701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Therapeutic Ultrasound on the Regeneration of Skeletal Myofibers After Experimental Muscle Injury

Abstract: Therapeutic ultrasound is used by many in the treatment of muscle injuries, but no previous attempts to objectively assess its effects on regenerating skeletal myofibers have been published. In this descriptive study, we followed the regeneration of contusion injury to the rat gastrocnemius muscle during treatment with pulsed ultrasound. The speed of myoregeneration in ultrasound-treated animals was compared with that in control animals by immunohistochemical, morphometric, and scintigraphic analyses. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
2
15

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 26 publications
2
83
2
15
Order By: Relevance
“…Several studies have shown that low-intensity US (LIUS) is effective in regenerating injured tissues, including muscles (3,4) and bones (5)(6)(7)(8)(9). In particular, LIUS has been shown to enhance the healing of fractured bones by inducing chondrocyte proliferation (7,9).…”
mentioning
confidence: 99%
“…Several studies have shown that low-intensity US (LIUS) is effective in regenerating injured tissues, including muscles (3,4) and bones (5)(6)(7)(8)(9). In particular, LIUS has been shown to enhance the healing of fractured bones by inducing chondrocyte proliferation (7,9).…”
mentioning
confidence: 99%
“…Although there is no promising animal or clinical evidence that US can help repair muscle injuries [20][21][22][23] , there is plenty of evidence showing the effects of US in collagen repair and re-synthesis 25,[33][34][35][36][37][38][39][40][41] . The use of US in the present clinical case was oriented at improving muscle collagen extracellular matrix (CEM) repair, based upon US effects on fibroblast proliferation and collagen synthesis 25,39) .…”
Section: Discussionmentioning
confidence: 99%
“…Although therapeutic ultrasound (US) is normally recommended for muscle skeletal rehabilitation 20,21) , the scientific evidence from animal studies is not promising 20,22,23) . However, these previous studies focused on myofibrillar changes rather than fibroelastic components such as the muscle extracellular collagen matrix, which has an important role in muscle force production 6,7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In various cell lines ultrasound treatment has been shown to lead to cell proliferation [1,2], enhanced protein activity, enhanced endocytosis [3] and several other biochemical effects [4][5][6]. Some of the beneficial effects of ultrasound upon wound healing have been attributed to inducement of angiogenesis-related cytokine production, increased nitric oxide production and calcium intake [7][8][9].…”
Section: Introductionmentioning
confidence: 99%